An analysis of interaction patterns in students' research essay guidance to build six main parameters of the Indonesian National Qualification Framework: Covid-19 pandemic period - Rosidin, Undang; Setyarini, M.; Widyastuti, Widyastuti (Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
This study aims to reveal the interaction patterns and inhibiting factors for the final project guidance in the Mathematics and Natural Sciences Education Department, Universitas Lampung, to develop the six main parameters of the Indonesian National Qualifications Framework (INQF). The study employed a mixed method involving 67 students who composed the final project for the 2021/2022 academic year selected from 314 final project students using the cluster random sampling technique. The data in this study were primary and secondary data obtained by questionnaires, interviews, and documents, analyzed qualitatively, quantitatively, and descriptively. The closed-response questionnaire was used regarding the interaction pattern, the INQF parameters achievement, and perceptions of the achievement of students' core competencies. An open-response questionnaire regarding the inhibiting factors for the final project guidance was used to provide the qualitative data. Descriptive analysis was conducted to determine the profile and interaction pattern of the final project guidance, while the qualitative analysis using Miles and Huberman model was to reveal the inhibiting factors of the final project. The results show that: (1) the dominant interaction pattern that occurred was an associative pattern originating from the factors of suggestion, identification, and sympathy; (2) the INQF parameter with the best score is the science parameter with an average parameter achievement of 9.97 from the lowest score 3.00 until the highest score 12.38; and (3) the perception of achieving the highest core competency of students is the aspect of soft skills, both personal and interpersonal, with the highest average perception of achieving core competency being 59.71 out of 80.